2010
DOI: 10.1177/070674371005500505
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Mental Health of Francophones in Canada, France, and Belgium: 12-Month and Lifetime Rates of Mental Health Service Use (Part 2)

Abstract: Objectives: To compare 12-month and lifetime service use for common mental disorders in 4 francophone subsamples using data from national mental health surveys in Canada, Quebec, France, and Belgium. This is the second article in a 2-part series comparing mental disorders and service use prevalence of French-speaking populations. Methods: Comparable World Mental Health-Composite International Diagnostic Interviews (WMH-CIDI) were administered to representative samples of adults (aged 18 years and older) in Can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 48 publications
0
3
0
1
Order By: Relevance
“…Few studies compared treatment-seeking between countries or by geographic region within countries, and those that did reported inconsistent findings [ 49 , 57 , 59 , 78 , 96 , 97 ]. There was a dearth of published evidence on the association between the health care environment and utilisation of services for CMD, with just one study on the effect of managed care [ 53 ], one on perceived availability of services [ 50 ], and one on perceived accessibility of services [ 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…Few studies compared treatment-seeking between countries or by geographic region within countries, and those that did reported inconsistent findings [ 49 , 57 , 59 , 78 , 96 , 97 ]. There was a dearth of published evidence on the association between the health care environment and utilisation of services for CMD, with just one study on the effect of managed care [ 53 ], one on perceived availability of services [ 50 ], and one on perceived accessibility of services [ 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…Living in an urban or rural area was not related to help-seeking behaviour in Spanish [41], Ethiopian [42], Canadian [38, 44] or American [32] samples. Additionally, no differences in help-seeking behaviour were found between the American and Canadian samples [40] or between the Francophone Canadian and European samples [67]. Differences in individuals’ help-seeking behaviour between different regions of the US were found in one [32] of two studies [31].…”
Section: Resultsmentioning
confidence: 99%
“…1 An examination of access to mental health services by French-speaking language minority individuals or Francophones in Canada (including Quebec) showed that most Francophones with mental disorders do not seek treatment. 2 However, Canadian Francophones were more likely to consult mental health professionals than their European counterparts, with the exception of psychiatrists. An important question is whether the level or quality of services received by those accessing mental health services varies as a function of membership in a minority language group in Canada.…”
Section: Introductionmentioning
confidence: 99%